Utilization of the Organ Care System – A Game-Changer in Combating Donor Organ Shortage - Popov, Aron-Frederik (Med Sci Monit Basic Res, 2015)
For patients with end-stage heart failure, cardiac transplantation persists to be the gold standard. Nevertheless, the availability of organs remains a main constraint to the treatment. Through mounting usage of ex vivo heart perfusion an increase in organ availability was achieved by reconditioning of organs formerly not regarded as appropriate for transplantation. We propose the future standard application of this state-of-the-art technology to improve the pool of donor organs by evaluating hearts outside standard acceptability criteria.